Expression of the pupal determinant broad during metamorphic and neotenic development of the strepsipteran Xenos vesparum Rossi - Erezyilmaz, D; Hayward, A; Huang, Y; Paps, J; Acs, Z; Delgado, J; Collantes, F; Kathirithamby, J (Public Library of Science, 2014)
Derived members of the endoparasitic order Strepsiptera have acquired an extreme form of sexual dimorphism whereby males undergo metamorphosis and exist as free-living adults while females remain larviform, reaching sexual maturity within their hosts. Expression of the transcription factor, broad (br) has been shown to be required for pupal development in insects in which both sexes progress through metamorphosis. A surge of br expression appears in the last larval instar, as the epidermis begins pupal development. Here we ask if br is also up-regulated in the last larval instar of male Xenos vesparum Rossi (Stylopidae), and whether such expression is lost in neotenic larviform females. We clone three isoforms of br from X. vesparum (Xv'br), and show that they share greatest similarity to the Z1, Z3 and Z4 isoforms of other insect species. By monitoring Xv'br expression throughout development, we detect elevated levels of total br expression and the Xv'Z1, Xv'Z3, and Xv'Z4 isoforms in the last larval instar of males, but not females. By focusing on Xv'br expression in individual samples, we show that the levels of Xv'BTB and Xv'Z3 in the last larval instar of males are bimodal, with some males expressing 3X greater levels of Xv'br than fourth instar femlaes. Taken together, these data suggest that neoteny (and endoparasitism) in females of Strepsiptera Stylopidia could be linked to the suppression of pupal determination. Our work identifies a difference in metamorphic gene expression that is associated with neoteny, and thus provides insights into the relationship between metamorphic and neotenic development.